2018
DOI: 10.17507/jltr.0902.13
|View full text |Cite
|
Sign up to set email alerts
|

Looking at the Shared Conception of Teaching Literature in an Indonesian ELT Setting

Abstract: Abstract-This paper uses the Interpretative Phenomenological Method to examine the conceptions thatEnglish literature teachers (ELITES) share about literature courses and teaching. The study investigated the experiences of four ELITES who taught literature classes at English education base faculties in three universities in Indonesia. These teachers were interviewed and observed in relation to their subject-matter knowledge in literature, their methods of teaching, their roles and the extent of their students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…2021, p.113-121 ISSN: 2446 teaching the humanities from the standpoint of postmodern pedagogy. Sunardi (2018) notes that when studying world literature due to limited knowledge of the original language, it is difficult for students to fully and comprehensively understand the deep meaning of literary and artistic text, especially classical literature. Also, when studying world literature, difficulties arise due to genre diversity, individual author's style, jargon and creative methods (BERRARBI, BAHOUS, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…2021, p.113-121 ISSN: 2446 teaching the humanities from the standpoint of postmodern pedagogy. Sunardi (2018) notes that when studying world literature due to limited knowledge of the original language, it is difficult for students to fully and comprehensively understand the deep meaning of literary and artistic text, especially classical literature. Also, when studying world literature, difficulties arise due to genre diversity, individual author's style, jargon and creative methods (BERRARBI, BAHOUS, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature is a resource viewed as a culturally valued text that is reflecting human life (Sunardi, Arafah, & Salija, 2018). Wellek and Warren (1956) also state that literature is a social institution that reflects the phenomena of social behavior in society using language as its media to express the author's thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…The text of a literary work will be meaningful and give complete information if it is observed in its context, such as by studying the cultural discourse (Arafah, Thayyib, Kaharuddin, & Sahib, 2020.) It also aims to engage the study of personal, cultural, societal, and aesthetic values as an attempt to understand human experiences in this life (Sunardi, Arafah, & Salija, 2018). It can be concluded that literature is a product of art in society.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by Yunus and Suliman (2014) who argued that teachers lack ideas in making literature lessons a meaningful one. On the other side, students might face difficulties in engaging with literary texts due to their language competency and proficiency as demonstrated by Novianti (2016) and Sunardi, Akil, Arafah and Salija (2018) who found that limited language proficiency impedes students in understanding literary texts, especially classical texts.…”
Section: Introductionmentioning
confidence: 99%